Surviving in the Amazon Arc of Deforestation: Richness and Defaunation of Mammals in Priority‐Protected Areas of the Brazilian Midwest - Melo‐Dias, Mateus [UNESP]; Ribeiro, Letícia G. [UNESP]; Queiroz, Julia F.; Penhacek, Marcos; Custódio, Rogério José; de Jesus Rodrigues, Domingos; Rosa, Clarissa (Wiley, 2025)
ABSTRACT The Amazon is recognised as one of the most conserved tropical rainforests in the world. However, along its peripheral agricultural frontiers, mammal assemblages are gradually being eroded due to deforestation of this large area known as the Arc of Deforestation, particularly along the Amazon's southeast. In this study, we aimed to expand on the knowledge of richness, composition, and defaunation of mammal assemblages in two priority protected areas for biodiversity in the region: Cristalino State Park (hereafter Cristalino) and Xingu State Park (hereafter Xingu). We used camera traps and line transects for data collection between 2020 and 2021. Our results demonstrated that both protected areas support rich assemblages of medium‐ and large‐sized mammals within the south‐central Amazon (Cristalino—32 species, Xingu—30 species). Due to the differing vegetation types between each park, the two mammal assemblages showed significant differences in species composition. Even with one of the highest biomasses of large ungulates (tapir and brocket deer) and apex predators (jaguar and puma) compared to other protected areas in south‐central Amazon, both areas showed a high biomass defaunation index relative to these same areas. The result is largely driven by the low abundance of peccaries, especially Tayassu pecari . This could be one of the impacts of extensive human pressure caused by deforestation and degradation around and inside these protected areas. Both parks play an important role in the survival of threatened mammals, and in maintaining biodiversity and ecosystem functionality in the southern Amazon, helping to curb agricultural expansion into the interior of the Amazon rainforest. RESUMO A Amazônia é reconhecida como uma das florestas tropicais mais bem preservadas do mundo. No entanto, ao longo de suas fronteiras agrícolas, as assembleias de mamíferos estão sendo gradualmente erodidas devido ao desmatamento dessa grande região conhecida como Arco do Desmatamento, particularmente ao longo do sudeste amazônico. Neste estudo, nosso objetivo foi ampliar o conhecimento sobre a riqueza, a composição e a defaunação dos mamíferos em duas unidades de conservação prioritárias para a biodiversidade na região: o Parque Estadual do Cristalino e o Parque Estadual do Xingu. Usamos armadilhas fotográficas e transectos lineares para a coleta de dados entre 2020 e 2021. Nossos resultados demonstraram que ambas as unidades de conservação apresentam assembleias de mamíferos de médio e grande porte ricas em espécies no centro‐sul da Amazônia (Cristalino – 32 espécies, Xingu – 30 espécies). Devido aos diferentes tipos de vegetação de cada parque, as duas assembleias de mamíferos apresentaram diferenças significativas na composição de espécies. Mesmo com uma das maiores biomassas de grandes ungulados (anta e veado‐mateiro) e predadores de topo (onça‐pintada e onça‐parda) em comparação com outras unidades de conservação no centro‐sul da Amazônia, ambas as áreas apresentaram um alto índice de defaunação de biomassa em relação a essas mesmas áreas. Este resultado, em grande parte, é causado pela baixa abundância de pecarídeos, especialmente Tayassu pecari . Esse pode ser um dos impactos da extensa pressão humana causada pelo desmatamento e pela degradação ao redor e dentro dessas unidades de conservação. Ambos os parques desempenham um papel importante na sobrevivência de mamíferos ameaçados de extinção e na manutenção da biodiversidade e funcionalidade do ecossistema no centro‐sul amazônico, ajudando a conter a expansão agrícola para o interior da Floresta Amazônica.